Unleashing the power of IT : bringing people, business, and technology together - Roberts, Dan (Dan D.), 1963- (Hoboken : Wiley, 2013)
"Go from the "IT guy" to trusted business partnerIf you're in IT, quite a lot is expected of you and your team: be technologically advanced, business-minded, customer-focused, and financially astute, all at once. In the face of unforgiving competition, rampant globalization, and demanding customers, business leaders are discovering that it's absolutely essential to have a strong, active partner keeping a firm hand on the decisions and strategies surrounding information technology. Unleashing the Power of IT provides tangible, hard-hitting, real-world strategies, techniques, and approaches that will immediately transform your IT workforce and culture, presenting the new mindset, skill set, and tool set necessary for IT leaders to thrive in today's challenging environment. Includes new discussion on social media Offers online access to the IT Skill Builder Competency Assessment Tool Features top ten lists of tips and techniques, proven frameworks, and practical guidance to help you launch and sustain your IT culture change and professional development initiatives Profiling several world-class organizations that have implemented the principles in this book, Unleashing the Power of IT reveals the best practices to get you on the path to implementation"--
Chapter 6 Negotiating: Getting What You Want without Damaging the RelationshipPosition versus Interest Negotiations; Three Steps and Three Key Factors; Negotiation Elements; People and Relationships; Styles and Situations; Applying the Key Factors to the Second Step: Information Exchange; The Final Step: Now Comes the Bargaining; Conclusion; Chapter 7 Sharpening Your Political Savvy; Picturing Yourself as a Political Player; IT and Politics: Historically Strange Bedfellows; A Five-Step Process for Developing Political Awareness; Start Your Radar; Determine Where the Power Bases Are
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Information technology -- Management; BUSINESS & ECONOMICS / Information Management; Information technology -- Management; Electronic books; Electronic books